Preparation and placement of cartilage island graft in tympanoplasty - Yurttas,Veysel (2014)
Introduction: Cartilage graft tympanoplasty has a better success rate in the treatment of chronic otitis media if regularly prepared and placed. Objective: To prepare cartilage island material and evaluate its effect on the success rate of tympanoplasty. Methods: The medical records of 87 patients (48 males and 39 females; mean age, 27.3 ±11.2 years; range, 14–43 years) with chronic otitis media without cholesteatoma who underwent intact canal-wall-up tympanoplasty and revision surgery between December of 2007 and October of 2011 were retrospectively evaluated. Surgery was performed under general anesthesia via a retroauricular approach. Results: The overall success rate of this technique was 93% in terms of perforation closure. No graft lateralization or displacement into the middle ear occurred. The overall average preoperative air bone gap was 37.27 ± 12.35 dB, and the postoperative air bone gap was 27.58 ± 9.84 dB. The mean postoperative follow-up period was 15.3 months (range: 7–21 months). Conclusion: If cartilage graft is properly prepared and placed, cartilage graft tympanoplasty appears to provide better success rates and hearing results.